Optimum Adaptive Modulation and Channel Coding Scheme for Frequency Domain Channel-Dependent Scheduling in OFDM Based Evolved UTRA Downlink - Miki, N.; Kishiyama, Y.; Higuchi, K.; Sawahashi, M. (2007 IEEE Wireless Communications and Networking Conference, 2007)
In the evolved UTRA (UMTS terrestrial radio access) downlink, orthogonal frequency division multiplexing (OFDM) based radio access was adopted because of its inherent immunity to multipath interference and flexible accommodation of different spectrum arrangements. This paper presents the optimum adaptive modulation and channel coding (AMC) scheme for simultaneously assigned resource blocks (RBs) for the same user when frequency and time domain channel-dependent scheduling is used in the downlink OFDMA radio access with single-antenna transmission. Theoretical analyses and simulation results show that, irrespective of the application of power adaptation to RB-dependent modulation, the improvement in the achievable throughput of the RB-dependent modulation scheme compared to that for the RB-common modulation scheme is slight, i.e., 4 to 5%. In addition, the number of required control signaling bits in the RB-dependent modulation scheme becomes greater than that for the RB-common modulation scheme. Therefore, the authors conclude that the RB-common modulation and channel coding rate scheme is preferred, when multiple RBs of the same coded stream are assigned to one user in the case of single-antenna transmission.